Control of Tip Rotation - Tasman, Abel-Jan; Lohuis, Peter J.F.M. (Facial Plastic Surgery, 2012)
Rotating the nasal tip is an integral and challenging aspect of rhinoplasty. This article describes ways of measuring tip rotation, coming to an agreement with the patient regarding desired tip rotation and psychological implications of tip rotation. Based on the tripod theory of the nasal tip, various techniques for changing tip rotation and projection are detailed and illustrated with clinical cases. The authors review the literature and present their personal preferences.
Keywords: rhinoplasty; nasal tip; tripod theory; tip sutures; patient psychology